Human Resource Management In A Coffee Beverage Sme To Gain Competitive Advantage In Indonesia - Robertus Romario; Sekar Wulan Prasetyaningtyas; Anita Maharani (Universitas Mercu Buana, 2021)
As a developing country, SMEs play an important role in Indonesia’s economy development. The prevalence of food and beverages SMEs in Indonesia is on the rise and on a tight competition, specifically coffee business. Inevitably, for the last couple of years, the number of new SMEs focusing on coffee beverage business is on the rise. Gaining a competitive advantage is essential for SMEs to achieve sustainability and profitability. There has been a dearth of studies on researching the importance of strategic human resource management to gain competitive advantage specifically for SMEs. Thus, this study aims to fill the gap in the literature on the topic and aims to assist entrepreneurs and SME founders in gaining competitive advantage through strategic human resource management. This study explores Kopi Soe, one of the most successful and leading coffee beverage SME in Indonesia on how Kopi Soe has been strategically manage its human resource to gain competitive advantage among its competitors. This study utilizes in-depth interview to collect data as qualitative method with Kopi Soe’s founders and employees to capture the human resource experience and how effective human resource management has been successfully putting them as the top coffee beverage SME in Indonesia in two years. The study found that Kopi Soe’s high involvement of human resource management positively increases competitive advantage through both innovative performance and entrepreneurial performance. Moreover, since most of the employees are millennials, this study also includes managerial implications on how to manage millennials in SMEs.